PROGNOSIS OF INHALATION INJURY IN SEVERE BURN PATIENTS ON EMERGENCY PHASE - Laksmi, Ida Ayu Agung (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Inhalation injury in severe burns is a serious problem cause mortality and morbidity. Survival prognosis of severe burn is most important for patients and family in the emergency phase. The purpose of this study is to analyze the impact of inhalation injury in severe burn patient during emergency phase in Sanglah Hospital, Bali, Indonesia. Methods: This study was a cohort retrospective design of the 78 samples of medical records at Sanglah Hospital in a period of 2 years, from March 2014 until March 2016. Results: The results of logistic regressions with mediation show that inhalation injury is a predictor factor of patientâs survival (p = 0.000) that mediated by respiratory rate. The equation obtained yâ = -6.608 + (5.589) (Inhalation Injury) + (1.942) (RR). The probability for patient with severe burn to die in the first 48 hours if the patient has an inhalation injury and has a respiratory rate in the first 8 hours after fluid resuscitation of more than 24 x/m is 71.4%. Conclusions: Patient with inhalation injury on severe burn has better prognosis if respiratory rate on first 8 hours is less than 24 cycles per minute.Â